Analyzing the labor market activity of immigrant families in Germany - Leilanie Basilio; Thomas K. Bauer; Mathias Sinning (Institute for the Study of Labor (IZA), 2007)
This paper analyzes whether immigrant families facing credit constraints adopt a family investment strategy wherein, upon arrival, an immigrant spouse invests in host country-specific human capital while the other partner works to finance the family's current consumption. Using data for West Germany, we do not find evidence for such a specialization strategy. We further examine the labor supply and wage assimilation of families whose members immigrated together relative to families whose members immigrated sequentially. Our estimates indicate that this differentiation is relevant for the analysis of the labor market activities of migrant households.
Keywords: 330; Migranten; Familienökonomik; Haushaltsökonomik; Soziale Integration; Schätzung; Deutschland